The dual effect of selenium application in reducing Fusarium wilt disease incidence in banana and producing se-enriched fruits - Liu, Lina; Wang, Chengye; Yin, Kesuo; Ni, Ming; Ding, Yue; Li, Chengyun; Zheng, Sijun (MDPI, 2024)
Fusarium wilt disease severely constrains the global banana industry. The highly destructive disease is caused by Fusarium oxysporum f. sp. cubense, especially its virulent tropical race 4 (Foc TR4). Selenium (Se), a non-essential mineral nutrient in higher plants, is known to enhance plant resistance against several fungal pathogens. The experiments we conducted showed that selenium (≥10 mg/L) dramatically inhibited the growth of Foc TR4 mycelia and promoted plant growth. The further study we performed recorded a substantial reduction in the disease index (DI) of banana plants suffering from Foc TR4 when treated with selenium. The selenium treatments (20~160 mg/L) demonstrated significant control levels, with recorded symptom reductions ranging from 42.4% to 65.7% in both greenhouse and field trials. The DI was significantly negatively correlated with the total selenium content (TSe) in roots. Furthermore, selenium treatments enhanced the antioxidant enzyme activities of peroxidase (POD), polyphenol oxidase (PPO), and glutathione peroxidase (GSH-Px) in banana. After two applications of selenium (100 and 200 mg/plant) in the field, the TSe in banana pulps increased 23.7 to 25.9-fold and achieved the Se enrichment standard for food. The results demonstrate that selenium applications can safely augment root TSe levels, both reducing Fusarium wilt disease incidence and producing Se-enriched banana fruits. For the first time, this study has revealed that selenium can significantly reduce the damage caused by soil-borne pathogens in banana by increasing the activities of antioxidant enzymes and inhibiting fungal growth.